Focal portal vein stenosis in an adolescent potentially related to complicated umbilical catheter insertion in the neonatal period. Issue 4 (31st May 2013) - Maleux, Geert; Hoffman, Ilse; Heye, Sam; Cassiman, David
A 14-year-old girl, with no medical history except for a preterm birth at 7 months, presented with clinical and laboratory signs of pancytopenia. Radiological investigation, including abdominal ultrasound and magnetic resonance imaging revealed a focal irregular main portal vein wall and splenomegaly. Endoscopy showed major esophageal and gastric varices. Definitive diagnosis was made by direct, transhepatic portography revealing a focal stenosis associated with a dissection of the main portal vein. Percutaneous treatment including balloon angioplasty and stent placement resulted in complete re-expansion of the portal vein main branch. Clinical and radiological follow-up over 5 years showed complete disappearance of all clinical signs and normalization of laboratory data and splenic volume.